Effect of Biologic Nurturing Baby Led Feeding on Post Sectio Caesarea Pain Scale In Majenang Hospital 2018 - Reni Cahyanti; Sinar Pertiwi; Etin Rohmatin (Poltekkes Kemenkes Semarang, 2020)
Background: Post SC pain are the caused by the uterus contracts roomates state continuously in the uterine involution and pain from surgical incision. Pain management can be done by non-pharmacologically and pharmacologically to reduce pain symptoms that Appear. One of the non-pharmacological methods to reduce pain in post SC is Biologic Nurturing Baby Led Feeding position. Biologic Nurturing Baby Led Feeding position is breastfeeding by lying position while leaning in 15°- 64°angle with the baby placed on the chest naturally.Methods: The research method used was a quasi-experimental design with one group pretest posttest. The population in this study was the maternal caesarean section in Majenang General Hospital, Cilacap Regency, with a sample that was purposive sampling technique, the number of samples was 40 respondents.Result: The results of the study showed that most of the pain before the Biologic Nurturing Baby Led Feeding had moderate pain as many as 27 people (67.5%) and after the biologic nurturing baby led feeding, most had mild pain as many as 27 people (67.5 %), influence on the pain of the sectio caesarea in the Majenang General Hospital with r value(0.000).Conclusion: It was suggested that Standard Operating Procedures (SOPs) regarding Biologic Nurturing Baby Led Feeding implementation in post partum ward was developed to help decreasing pain in postpartum client with SC.